The formation and development of pedagogical education in the South Ukraine in the middle of the XIX – beginning of the XX century - Марків, Володимир Миколайович (Pedagogy of Higher and Secondary Education, 2019)
Markiv V. N. The formation and development of pedagogical education in the South Ukraine in the middle of the XIX – beginning of the XX century. The article examines the sources of enrichment of the theory and practice of national educational system development its formation and development of pedagogical education of the southern region of Ukraine in the middle of the XIX – beginning of the XX century. Socio-economic and social and political changes should cause the distinctive development of professional education, including pedagogical, its major tendencies; they demanded the reforming of the educational processes, higher organization and improvement. Undoubtedly, educational reforms were of class character and conducted in the interests of the nobility and the emerging bourgeoisie.